Assessment of Green Extraction Techniques in the Utilization of Oak Tree (Quercus robur) and Mugwort (Artemisia vulgaris) Biomass for the Production of Bioactive Extracts - David Villanueva-Bermejo; Diego Martín Hernández; Elvis Judith Hernández; Susana Santoyo; Tiziana Fornari (Separations)
The aim of this study was to investigate the suitability of Pressurized Liquid Extraction (PLE) and Supercritical Fluid Extraction (SFE) for Quercus robur bark and Artemisia vulgaris extraction. PLE of Q. robur and A. vulgaris were carried out at different temperatures with water, ethanol and several hydroalcoholic mixtures. SFE of A. vulgaris was performed at different pressures and ethanol concentrations. The anti-inflammatory activity of Q. robur extracts, the antibacterial activity of A. vulgaris extracts and the antioxidant activity of the extracts from both materials were determined. The highest phenolic compound content and antioxidant activity of Q. robur extracts were achieved with water at 100 °C (487.97 mg GAE/g and 3741 µg trolox/g). The highest values for A. vulgaris extracts were obtained with ethanol at 200 °C (149.16 mg/g and 437.13 µmol/g). The ethanolic extract at 150 °C from A. vulgaris had a noticeable anti-inflammatory activity (inhibition of TNF-α and IL-6 secretion near basal values and inhibition of IL-1β higher than 80% at 20 µg/mL). A. vulgaris extracts obtained by SFE exerted antibacterial activity against E. coli (IC50 of 1388 µg/mL with neat SCCO2 at 15 MPa) and S. aureus (1406 µg/mL using SCCO2 with 10% ethanol).